KETERAMPILAN SOSIAL EKS PSIKOTIK DI RUMAH SINGGAH DOSARASO KABUPATEN KEBUMEN PROVINSI JAWA TENGAH: Bahasa Indonesia - Anwar Sanusi; Nono Sutisna; Muhamad Ananta Firdaus (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
Social skills refer to the basic abilities that every individual must have in carrying out social processes in society. This study aims to obtain an in-depth description of : 1) interaction, 2) communication, and 3) participation of ex-psychotics. This study used a descriptive qualitative method with data collection techniques: 1) in-depth interviews, 2) observation, and 3) documentation study. The data sources in this study are primary data sources from officers at the Dosaraso Halfway House and secondary data sources in the form of documentation or other information. As for checking the validity of the data, it was carried out using a credibility test through observation persistence, triangulation, and adequacy of references, as well as dependability testing. The results showed that the social skills of ex-psychotics at the Dosaraso Halfway House were not maximized. Based on the three aspects, the results that show quite good are the communication aspects, while what is quite lacking is the interaction aspects, and what is still lacking is the participation aspect.